Analisis UU No. 34 Tahun 2004 Tentang Kedudukan dan Peran TNI dalam Lembaga Pemerintahan Negara - Muhammad Hendrik Novavah (Sharia Faculty, Kiai Haji Achmad Siddiq State Islamic University of Jember, 2020)
The military in Indonesia has been heavily involved in socio-political life in determining state policy. This involvement in the socio-political realm that began in 1945-1998 was known as the dual function of ABRI. However, the concept of ABRI's dual function is seen as the cause of the failure of the existing government system in Indonesia. With the many demands for reform and the fall of the New Order regime, in 2000 to be precise in May the concept of Dwifungsi was officially removed from the treasury of the TNI institution. The type and approach used in this research is normative legal research. The approach used is the statute approach, the case approach, and the conceptual approach. Sources of research using primary legal materials and secondary legal materials. Collection of legal materials, namely, looking for legal materials that are relevant to the issue at hand. Analysis of legal materials using deductive and inductive methods.